Effects of Public Debt on Economic Growth of Nepal - Sapkota, Piamber (The Lumbini Journal of Business and Economics, 2023)
This study aims to analyze the effect of public debt dividing into internal and external debt on economic growth rate of Nepal using time series data from 1990 – 2021 A.D. The Autoregressive Distributed Lag (ARDL) model is employed to investigate the effect as well as long – run and short – run relationship between economic growth and public debt. It is found that in long run, effect of internal debt upon the economic growth rate of Nepal is negative. Similarly, the long run effect of external debt upon the economic growth rate is positive and significant. The short run effect analysis result also shows that effect of external debt upon economic growth rate is positive. It indicates that effect of external debt upon economic growth rate is consistent in both long-run and short-run. Furthermore, the results show that there is also the long run relationship between the economic growth rate (i.e. RGDPgr) and internal debt, external debt. Similarly, the result of ECM analysis shows that there is also short-run relationship between economic growth rate and internal debt, external debt. Moreover, there is not found strong effect of public debt on economic growth of Nepal.